Migration: A Process of Search - London A Case Study - Flores, Nubia Zulma Nieto (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2024)
TV news, social media, and newspapers continue presenting migrants as a threat to the rich economies. However, the richness of cosmopolitan cities is the migration. London, the capital of the United Kingdom, is a case in point. In this context, the present article is guided by the following research question: what are the main causes of migration to London? This text has as objective to explore the drivers behind of migration to London. The hypothesis is based on the assumption that people who migrate to London have different motivations and not necessarily economic reasons. This work uses qualitative and quantitative materials, such as face to face interviews, data reports and statistics on migration and direct observations. This article is divided in four sections. The first one exposes some outstanding theories on migration. The second one describes the methodology applied. The third one offers some personal experiences of migrants living in London. The fourth one presents some results about the main drivers of migrants to London, and finally some conclusions are offered, which consider that there are subtle causes of emigration which are usually underestimated, such as learning English as a personal achievement, acceptance of different sexual orientation, cultural diversity, and relative political stability are among the most representative.